Electrochemically Exfoliated Layered Carbons as Sustainable Anode Materials for Lead Carbon Hybrid Ultracapacitor. Issue 11 (1st June 2022) - Muduli, Sadananda; Pappu, Samhita; Bulusu, Sarada V.; Rao, Tata N.; Martha, Surendra K.
Abstract: Lead‐carbon hybrid ultracapacitors (Pb−C HUC) have become apparent as a way out of the sulfation issue of lead‐acid batteries, simultaneously enhancing the system's power density and cycle life. In this work, exfoliated graphene oxides (EGO) were synthesized by the electrochemical exfoliation method followed by chemical activation and carbonization at 600 °C (AEGO‐600). The composite electrode delivered 800 F g −1 capacitance at 1 A g −1 . The Pb−C HUC fabricated using AEGO‐600 anode and PbO2 cathode can achieve capacitance of 325 F g −1 at 10 A g −1 and retain 71 % capacitance after 15000 charge‐discharge cycles in the voltage range of 2.3–0.8 V. The highly stable capacitance was due to the formation of layered carbons in AEGO‐600 that enhanced the favorable electrolyte ion assessment to maximum active sites. Owing to the facile, cost‐effective synthesis approach and better charge storage behavior, the activated‐exfoliated graphene oxides thus produced could be suitable candidates for future hybrid ultracapacitor systems. Abstract : Lead‐carbon hybrid ultracapacitor : Activated exfoliated graphene oxide (AEGO‐600) synthesized by the electrochemical exfoliation method followed by chemical activation and carbonization at 600 °C was used as anode material for lead‐carbon hybrid ultracapacitors. The highly stable capacitance was due to the formation of layered carbons in AEGO‐600 that enhanced the favorable electrolyte ion assessment to maximum active sites.